Eleven biosynthetic genes explain the majority of natural variation in carotenoid levels in maize grain. Issue 4 (2nd December 2020) - Diepenbrock, Christine H; Ilut, Daniel C; Magallanes-Lundback, Maria; Kandianis, Catherine B; Lipka, Alexander E; Bradbury, Peter J; Holland, James B; Hamilton, John P; Wooldridge, Edmund; Vaillancourt, Brieanne; Gngora-Castillo, Elsa; Wallace, Jason G; et al.
Abstract: Vitamin A deficiency remains prevalent in parts of Asia, Latin America, and sub-Saharan Africa where maize ( Zea mays ) is a food staple. Extensive natural variation exists for carotenoids in maize grain. Here, to understand its genetic basis, we conducted a joint linkage and genome-wide association study of the US maize nested association mapping panel. Eleven of the 44 detected quantitative trait loci (QTL) were resolved to individual genes. Six of these were correlated expression and effect QTL (ceeQTL), showing strong correlations between RNA-seq expression abundances and QTL allelic effect estimates across six stages of grain development. These six ceeQTL also had the largest percentage of phenotypic variance explained, and in major part comprised the three to five loci capturing the bulk of genetic variation for each trait. Most of these ceeQTL had strongly correlated QTL allelic effect estimates across multiple traits. These findings provide an in-depth genome-level understanding of the genetic and molecular control of carotenoids in plants. In addition, these findings provide a roadmap to accelerate breeding for provitamin A and other priority carotenoid traits in maize grain that should be readily extendable to other cereals. Abstract : Eleven genes were identified for grain carotenoids by integrating joint-linkage, genome-wide association, RNA-seq, pleiotropy, and epistasis analyses of the US maize nested association mapping panel.